Mekanisme Kawalan Kesejahteraan Psikologi Berasaskan Metode al-Tafakkur Dalam Al-Quran: Psychological Well-Being Control Mechanisms Based on the Method of al-Tafakkur in the Qur'an - Rahim Kamarul Zaman; Khairulnazrin Nasir; Muhammad Adam Abd. Azid; Abdul Azib Hussain (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
The issue of the psychological well-being of society is a discourse that is increasingly given universal attention in the aftermath of the covid-19 pandemic. In the fourth quarter of 2020, a study by the Malaysian Public Service Department reported that the interpretation of the Malaysian psychological well-being index was at a moderate level with an overall score of 7.2. Among the key elements that are a measure of psychological well-being are emotional quality, self-actualization, life satisfaction, psychological functionality and the ability to interact with the environment. In this regard, initiatives to control the sustainability of psychological well-being are being actively pursued by various parties. Thus, the purpose of this study is to present a proposal for the control of psychological well-being control based on the method of al-tafakkur in the Quran. The study in the form of theory application is worked on the basis of qualitative methods through content analysis approach. The results of the study found that the discourse of the method of al-tafakkur in the Qur'an is holistic. The combination of the understanding is able to control and stabilize the mind or emotions. In conclusion, the Quran-based method of al-tafakkur should be dignified as part of the complementary mechanism of psychological well-being control.